Plasma-derived exosomal miR-326, a prognostic biomarker and novel candidate for treatment of drug resistant pediatric acute lymphoblastic leukemia - Neda Saffari; Soheila Rahgozar; Elaheh Faraji; Fikrettin Sahin (Scientific Reports)
Abstract Acute lymphoblastic leukemia (ALL) is a cancer with high incidence rate in pediatrics and drug resistance is a major clinical concern for ALL treatment. The current study was designed to evaluate the role of exosomal miR-326 in diagnosis and treatment of children with B-ALL. Exosomes were isolated from plasma samples of 30 patients and B-ALL cell lines followed by characterization, using nanoparticle tracking analysis, immunoblotting assay and electron microscopy. qPCR showed significantly increased levels of miR-326 in patients exosomes compared with non-cancer controls (P < 0.05, AUC = 0.7500). Moreover, a comparison between the sensitive and drug resistant patients revealed a prognostic value for the exosomal miR326 (P < 0.05, AUC = 0.7755). Co-culture studies on drug resistant patient primary cells and B-ALL cell lines suggested that exosomes with high miR-326 level act as vehicles for reducing cells viability. B-ALL cell line transfection with naked miR-326 mimic confirmed the results, and fluorescence microscopy validated uptake and internalization of exosomes by target cells. The novel introduced features of the exosomal miR-326 address a non-invasive way of diagnosing primary drug resistance in pediatric ALL and advocates a novel therapeutic strategy for this cancer.